Cabotagem no Brasil: análise estrutural e avaliação dos impactos econômicos e ambientais da Lei BR do Mar - Simões, Carolina de Lima (2025)
This dissertation aims to analyze coastal shipping (cabotage) in Brazil through two complementary approaches: the structure of the maritime logistics network and the economic and environmental impacts of public policy established by Law No. 14.301/2022 (BR do Mar). In the first part, complex network theory is applied to evaluate the connectivity among Brazilian ports, using topological indicators based on short-distance maritime flows. The results reveal a dense but highly concentrated network, dominated by key logistical hubs, highlighting the need for improved port decentralization. In the second part, a Computable General Equilibrium (CGE) model is employed—specifically the multiregional and multisectoral Brazilian Economic Analysis (BREA) model—to simulate productivity increase scenarios in cabotage (5%, 15%, and 30%). The estimated impacts include changes in GDP, welfare, household consumption, sectoral output, CO₂ emissions, and regional transport supply. The findings indicate moderate economic gains, regional inequality reduction, and significant emission decreases in areas heavily reliant on road freight. Sensitivity analysis confirms the robustness of the results. This dissertation contributes by integrating network analysis with economic modeling, offering empirical evidence to support the development of more effective and sustainable transport policies in Brazil.